Bufo bergi (Anura: Bufonidae): Reproduction. Natural History Notes - Schaefer, Eduardo Federico (2006)
BUFO BERGI (NCN). REPRODUCTION. Bufo bergi is associated with the flood plains of the Paraná and Paraguay rivers in northern Corrientes, eastern Chaco, Formosa, and northern and eastern Santa Fe, Argentina, and in adjacent southern Paraguay (Frost 2004 http://research.amnh.org/herpetology/amphibia/index.html). Few data are available to describe the reproductive traits of B. bergi. Fifteen individuals were captured in rice field habitat in Estancia La Norah (27°47´S, 58°46´W), 30 km S of Corrientes City, Corrientes Province</city />, Argentina</country-region /></place />. Males (N = 10) were collected between 1 Nov 2001 and 5 Nov 2003</date />; females (N = 5) were collected between 14 Oct 1999 and 19 Nov 2003. Specimens were captured in roadside ditches between 1800 and 2000 h, preserved in 10% formalin, and deposited at CECOAL (Centro de Ecología Aplicada del</place /></state /> Litoral). Males measured: 33.3 - 40.5 mm SVL (mean 36.6; SD 2.4; CV 6.6%), body mass (BM) was 3.7-8.5 g (mean 6.2; SD 1.5; CV 24.9%); testes mass was les s than 0.01 g. Testes were white in color and somewhat cylindrical in form. Females measured: 33.1-43.1 mm SVL (mean 40.4; SD4.7; CV 11.6%), net body mass (BM) (body mass ?ovary mass) was 5.1-9.8 g (mean 6.9; SD 2.0; CV 29.2%); ovary mass (OM) was 0.46-1.5 g (mean 0.7; SD 0.46; CV 62.5%); ovarian complement (OC) (number of mature ova) was 1043-2490 (mean 1751.8; SD 435.5; CV 24.9%); mature ova diameter (OD) was 0.30-0.70 mm (mean 0.5; SD 0.06; CV mean[5 females 11.17%; SD cv = 2.2%; N = 500); reproductive effort (RE) (ovary mass/body mass%) was 4.7-19% (mean 10.7%; SD 5.4%; CV 50.1%); ovarian size factor (OSF) ([mean OC * mean OD] / mean SVL gravid females) (Duellman and Crump 1974. Occas. PapoMus. Nat. Hist.Univ. Kansas</place /></state />. 23:140) was 18. Ova were dark pigmented. The differences in SVL and BM (net body mass for females) between males and gravid females were not significant (SVL [Mann-Whitney U-Test = 38.00; p = 0.11]; BM [Mann-Whitney U-Test = 29.00; P = 0.62]). Bufo bergi is an explosive breeder with breeding activity lasting one to a few days, with synchronous arrival of males and females. Table 1 summarizes the morphometric and reproductive features of males and females used in this study.